DEFENSE MECHANISM IN NO LONGER HUMAN (2019) MOVIE: A PSYCHOANALYTIC APPROACH - Setyo, Fakhry Tri; Nugroho, Abdillah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
This study explores Osamu Dazai's defense mechanisms as depicted in the film adaptation of No Longer Human (2019) from a psychoanalytic perspective, drawing on Sigmund Freud's theoretical framework. The narrative follows the protagonist's tumultuous journey, highlighting his struggles with identity, alienation, and social conformity. Using Freud's psychoanalytic concepts, including defense mechanisms such as denial, projection, displacement, sublimation, reaction formation, undoing, and isolation, this study examines the protagonist's psychological responses to trauma and guilt. Employing Miles and Huberman’s method of data reduction, data display, and conclusion drawing, the research conducts a close analysis of character behavior, dialogue, and symbolism. The film's depiction of these defense mechanisms offers profound insights into the human psyche and its coping strategies in the face of internal and external conflict. By integrating Freudian theory with cinematic interpretation, this study aims to elucidate the intricacies of Dazai's defense mechanisms and provide a deeper understanding of the complexity of human psychology as portrayed in the film.